Spoilage of fresh turkey and pork sausages: Influence of potassium lactate and modified atmosphere packaging. (November 2020) - Luong, Ngoc-Du Martin; Jeuge, Sabine; Coroller, Louis; Feurer, Carole; Desmonts, Marie-Hélène; Moriceau, Nicolas; Anthoine, Valérie; Gavignet, Sophie; Rapin, Adeline; Frémaux, Bastien; Robieu, Emeline; Zagorec, Monique; et al.
Graphical abstract: Highlights: High oxygen atmosphere increases off-odour and discolouration of turkey sausages. Unlike turkey, lactate barely affects spoilage-associated responses in pork sausages. Spoilage dynamics or pork and turkey sausages vary greatly between production batches. Abstract: Fresh poultry and pork meat products represent highly perishable products which are susceptible to spoil within a few days after production. Lactate addition and modified atmosphere packaging are common preservation strategies used to overcome spoilage. This study aimed to identify the effects of these strategies and their possible interactions on spoilage indicators simultaneously on fresh pork and turkey sausages. Ten batches of raw meat (turkey or pork) sausages were industrially produced with different lactate concentrations (0, 1 or 2% w/w in turkey and 0, 0.57 and 1.13% w/w in pork), packed under different gas mixtures (air, MAP1: 70% O2 – 30% CO2 and MAP2: 50% CO2 − 50% N2 ) and chill stored during 22 days. Spoilage responses including enumeration of total aerobic mesophilic and lactic acid bacteria, measurement of pH and colour, evaluation of visual defects and off-odour, were monitored. Effects of lactate and modified atmosphere packaging (MAP) as well as random effect of the batch variability were studied using a mixed effect model. Despite initial batch variability, significant effects of lactate and gas packaging were observed but in a different way in turkey and pork. Our results suggest that for fresh turkey sausages, the gas mixture enriched in oxygen enhanced off-odour perception and sausage discolouration from red to dark grey / brown colour. Unlike turkey sausages, in pork sausages, lactate did not significantly influence the monitored spoilage responses, whereas MAP (70% O2 -30% CO2 ) reduced the off-odour perception. The developed model could be useful to estimate the effect of preservation strategies on spoilage occurrence while considering industrial batch variability.